Transsphenoidal Surgery of Corticotroph Adenomas With Cavernous Sinus Invasion: Results in a Series of 86 Consecutive Patients - Dai, Congxin; Feng, Ming; Lu, Lin; Sun, Bowen; Fan, Yanghua; Bao, Xinjie; Yao, Yong; Deng, Kan; Wang, Renzhi; Kang, Jun (Frontiers in Oncology, 2022)
Objective: Transsphenoidal surgery (TSS) is first-line treatment for corticotroph adenomas, a small subset of them invading Cavernous Sinus (CS) is notoriously difficult to manage. The aim of this study was to evaluate surgical outcome of corticotroph adenomas with CSI from a single-center. Patients and Methods: The clinical, endocrinological, radiological, histopathological, surgical outcomes and a minimum 12-month follow-up of patients with corticotroph adenomas invading CS were retrospectively reviewed. Results: Eighty-six patients with corticotroph adenomas invading CS were included in the study. All included 86 patients were performed TSS by microscopic or endoscopic approach. Gross-total resection was achieved in 63 patients (73.3%), subtotal resection in 18 (20.9%), and partial resection in 5 (5.8%). After surgery, the overall postoperative immediate remission rate was 48.8% (42/86), 51.2 % (44/86) of patients maintained persistent hypercortisolism. In 42 patients with initial remission, 16.7 % (7/42) of them experienced a recurrence. In 30 patients with persistent disease and recurrent CD, the radiotherapy was used for 15 patients, and 4 (26.7%) of them achieved biochemical remission. Repeat TSS was performed in 5 patients, and none achieved remission. Medication was administrated in 4 patients, and one of them obtained disease control. Adrenalectomy was performed in 6 patients, and 5 (83.3%) achieved biochemical remission. At last follow-up, (33.3%) 10 of 30 patients were in remission, and 20 patients still had persistent disease. The remission rate in corticotroph adenomas with Cavernous Sinus invasion (CSI) that underwent gross-total resection and first TSS were significantly higher than that in patients undergoing subtotal resection, partial resection, and a second TSS (all P＜0.05). However, there was no significant difference in the remission rate between patient with different tumor size, Knosp Grade and surgical approaches (P＞0.05). Conclusion: The management of corticotroph adenomas with CSI remain a therapeutic challenge due to incomplete resection of invasive and/or a large adenoma. With application of multiple techniques assistance, approximately half of the patients could achieve gross-total resection and biochemical remission via TSS by experienced neurosurgeons. The extent of tumor resection and number of operations were associated with surgical remission rate in corticotroph adenomas with CSI.